Investigating ladybird (Coleoptera : Coccinellidae) alkaloids as novel sources for insecticides: differential inhibition of the vertebrate and invertebrate nicotinic acetylcholine receptor using harlequin ladybird (Harmonia axyridis) extract and synthetic hippodamine - Richards, David (2012)
Ladybird beetles (Coleoptera:Coccinellidae) are ubiquitous, being found on every continent with the exception of Antarctica, and inhabiting a huge range of habitats. Roughly 6000 sp. have been described, comprising at least 490 genera. When disturbed, ladybirds ‘reflex bleed’ (autohemorrhage) from the femoro-tibial joints, producing a viscous, yellow liquid which has a very distinctive odour, this has been shown to be an effective deterrent against predation from both birds and arthropods. Feeding trials have demonstrated that many ladybirds are considered unpalatable and unacceptable as food sources by many potential predators. The bright colouration displayed by many coccinellids is thought to function as an aposematic warning. This has been demonstrated experimentally using Japanese quails, where colour was shown to be a more effective feeding deterrent than either taste or smell. A number of novel compounds have been isolated from this fluid, including alkaloids. It has been hypothesised that alkaloids within the defensive fluid will serve a toxic function, and this is the basis of the aposematic colouration.